PERILAKU SOSIAL ANAK JALANAN DI KAWASAN SIMPANG 4 PASAR PAGI ARENGKA - Prasetya, Olaf; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
One of the social problems that exist in Indonesia, namely the increasing number of poor people in this country. One of the effects of poverty is disregard for the rights of children, which soon led to child labor. Child labor is a term for employing young children. The term child labor can have the connotation of exploitation anakkecil on their labor, with a small salary or consideration for their personality development, security, health and future prospects. Appropriate legislation, set a minimum working age of 13 years. So that working children under 13 years are also called child labor. Based on these data it can be estimated that the conditions of child labor in Indonesia is very bad, a lot of factors driving children to work, it is among the number of poor diIndonesia are still very high above 30 million, and the Consumer Price Index / High inflation, resulting in many child chooses to feed herself or help the family.Figure of street children sprung in the Pekanbaru city, be it on the roadside , on the intersection of traffic signs, and in other public areas. Street children make the place for their place to work as well as search for the sourch of life. Most of the children spent their time on the street. The research took a sample of 9 the Street Children who conduct their activities around at simpang 4 pasar pagi arengka Pekanbaru city.Tekhnik of collecting data obtained in the study through the interview and observation to 9 children street as respondent. The research shows that the factors encouraging children choice becoming street children, social behavior of street children and street children receive of violence.Keywords: Street Children, Social Behavior and Family.